ANALISIS PERENCANAAN KAPASITAS DENGAN METODE POHON KEPUTUSAN & DIAGRAM LINEAR DI UMKM ANDIKA FARM - Marlina, Winny Alna; Armijal, Armijal (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2024)
One micro, small, and medium enterprise (MSME) in the Payakumbuh City area is Andika Farm, which focuses on broiler chicken production. This MSME has distributed a lot of broiler chickens and is collaborating with other parties to increase its production. One of the problems faced by Andika Farm MSMEs is capacity planning, empty cages due to a shortage of seeds, disrupted distribution of chickens, and a lack of planning to meet needs. The research aims to help plan capacity by determining the amount of production, constraints that must be considered, optimal profits, and sensitivity values to the optimum solution achieved in MSMEs. This research was conducted using two methods: Linear Programming and Decision Trees. The results of optimizing cage profit 2 produce an EMV of IDR 104,500. Compared with cage 1, cage 2 has the best use of production factors. The quality of the seeds is greatly influenced by the cage's location, where production factors could be more efficient.Keywords: capacity planning; decision tree; linear Programming